2022
DOI: 10.1002/admt.202200337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Mode Engineering with Orthotropic Metamaterial Membranes

Abstract: Metamaterials are structures engineered at a small scale with respect to the wavelength of the excitations they interact with. These structures behave as artificial materials whose properties can be chosen by design, mocking and even outperforming natural materials, and making them the quintessential tool for manipulation of wave systems. In this paper it is shown how the acoustic properties of a silicon nitride membrane can be affected by nanopatterning. The degree of asymmetry in the pattern geometry induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…If elastic metamaterials are used, C 66 can be equal to or greater than C 11 , possibly allowing elastic wave manipulation in an unprecedented way. Lee et al [143] proposed off-centered double-void-slit metamaterials, as shown in figure 10(a perforating slit-shaped void holes in isotropic materials, but other methods have also been proposed [145][146][147][148]. Research on breaking the symmetry of the elasticity tensor by using active elements has also been reported [149][150][151].…”
Section: Extreme Anisotropic Materials Propertiesmentioning
confidence: 99%
“…If elastic metamaterials are used, C 66 can be equal to or greater than C 11 , possibly allowing elastic wave manipulation in an unprecedented way. Lee et al [143] proposed off-centered double-void-slit metamaterials, as shown in figure 10(a perforating slit-shaped void holes in isotropic materials, but other methods have also been proposed [145][146][147][148]. Research on breaking the symmetry of the elasticity tensor by using active elements has also been reported [149][150][151].…”
Section: Extreme Anisotropic Materials Propertiesmentioning
confidence: 99%